An Analysis of Foucauldian Power in Jojo Rabbit Movie (2019) - Anggi Rulina Sitnggang; E. Ngestirosa Endang Woro Kasih (Universitas Islam Negeri Palopo, 2026)
This research is titled Foucauldian power in the film Jojo Rabbit (2019). This research aims to uncover how Foucauldian power is depicted through Jojo from the movie Jojo Rabbit using Foucault's theory of the use of power. The analysis uses scenes, images, dialogues and narratives contained in the film, then looks for contextual similarities with Foucault's concept. A qualitative descriptive approach is applied in this study which includes the main data from the film, equipped with various references. Ten-year-old Jojo Betzler was educated by the Nazis to imagine Hitler, the Nazis, and the Aryans superior and the Jews considered weak. It was only when he met and befriended Else, a Jewish girl hiding in his attic, that he was able to break free and begin to recognize and deconstruct the superior and weak that he had imagined all along. This film contains all elements based on dialogue, main characters, scenes, images and narratives contained in the film. The findings of the study show that there are three important elements to reveal Foucault's power such as acceptance toward nazi ideology, power for protecting others and power for being acknowledged.